Early dynastic and early Sargonic tablets from Adab in the Cornell University Collections - Visicato, Giuseppe; Westenholz, Aage 1939- (Cornell University studies in Assyriology and Sumerology (CUSAS), 2010)
Adab calendar -- Early dynastic IIIa texts -- Early dynastic IIIa to IIIb texts -- Early dynastic IIIb texts from Adab -- Early dynastic IIIb to early Sargonic texts -- Texts from the time of Meskigalla -- Early Sargonic texts after Meskigalla -- Texts from Adab from the early Sargonic period -- Texts from other sites -- Appendix -- Indexes: Personal names -- Professions -- Deities -- Temples and sanctuaries -- Toponyms -- Institutions -- Fields and canals -- List of words discussed -- New signs -- Photographs of selected texts